2014
DOI: 10.1186/1471-2490-14-36
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of ezrin in urothelial bladder cancer signifies more advanced tumours and an impaired survival: validatory study of two independent patient cohorts

Abstract: BackgroundReduced membranous expression of the cytoskeleton-associated protein ezrin has previously been demonstrated to correlate with tumour progression and poor prognosis in patients with T1G3 urothelial cell carcinoma of the bladder treated with non-maintenance Bacillus Calmette-Guérin (n = 92), and the associations with adverse clinicopathological factors have been validated in another, unselected, cohort (n = 104). In the present study, we examined the prognostic significance of ezrin expression in uroth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 24 publications
4
19
1
Order By: Relevance
“…Non‐expression of ezrin has been more commonly observed in colorectal adenocarcinoma with poor prognostic factors, leading to late‐stage tumours and short survival times . Negative or weak ezrin expression in serous ovarian and urothelial bladder has also been reported, and correlated with poor patient outcome . Similarly, we have shown that, in CCAs, non‐expression or low expression of ezrin is more frequently observed in peripheral CCA than in perihilar CCA.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Non‐expression of ezrin has been more commonly observed in colorectal adenocarcinoma with poor prognostic factors, leading to late‐stage tumours and short survival times . Negative or weak ezrin expression in serous ovarian and urothelial bladder has also been reported, and correlated with poor patient outcome . Similarly, we have shown that, in CCAs, non‐expression or low expression of ezrin is more frequently observed in peripheral CCA than in perihilar CCA.…”
Section: Discussionsupporting
confidence: 67%
“…These data suggest a potential role of ezrin in cholangiocarcinogenesis. Indeed, ezrin expression has been analysed in several other human malignancies, and has been related to cancer progression and poor outcome …”
Section: Introductionmentioning
confidence: 99%
“…This conclusion is further strengthened by recent multiple observations that miR-144 is consistently downregulated in many different types of cancers [20][21][22]. The cytosolic protein Ezrin is a member of ERM (Ezrin, radixin, moesin) protein family which plays important roles in regulation of cell adhesion and in the linkage between membrane proteins and contributes to tumor progression and development promoting cell survival, migration, and invasion [23,24]. Ezrin is overexpressed in aggressive tumors, and its activity is controlled by several signaling pathways involved in metastasis.…”
Section: Introductionmentioning
confidence: 49%
“…Due to the potential importance of ezrin in cancer, the prognostic significance of ezrin has been evaluated in numerous types of cancers [13][14][15][16]. However, the results have been somewhat contradictory [15,17,18]. Recent meta-analyses have revealed that elevated ezrin expression is associated with poor prognosis in patients with a variety of solid tumors [19,20].…”
mentioning
confidence: 99%